An intra-textual study of Aristotle’s Nicomachean Ethics Book VI and the role of the five states of the rational soul - Swart, G.J. (Gerhardus Jacobus), 1955- (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2011.